Semaglutide in HFpEF across obesity class and by body weight reduction: a prespecified analysis of the STEP-HFpEF trial - Borlaug, Barry A; Kitzman, Dalane W; Davies, Melanie J; Rasmussen, Søren; Barros, Eric; Butler, Javed; Einfeldt, Mette Nygaard; Hovingh, G Kees; Møller, Daniél Vega; Petrie, Mark C; Shah, Sanjiv J; Verma, Subodh; et al. (Nature medicine, 2023)
In the STEP-HFpEF trial, semaglutide improved symptoms, physical limitations and exercise function and reduced body weight in patients with obesity phenotype of heart failure and preserved ejection fraction (HFpEF). This prespecified analysis examined the effects of semaglutide on dual primary endpoints (change in Kansas City Cardiomyopathy Questionnaire-Clinical Summary Score (KCCQ-CSS) and body weight) and confirmatory secondary endpoints (change in 6-minute walk distance (6MWD), hierarchical composite (death, HF events, change in KCCQ-CSS and 6MWD) and change in C-reactive protein (CRP)) across obesity classes I-III (body mass index (BMI) 30.0-34.9 kg m-2, 35.0-39.9 kg m-2 and ≥40 kg m-2) and according to body weight reduction with semaglutide after 52 weeks. Semaglutide consistently improved all outcomes across obesity categories (P value for treatment effects × BMI interactions = not significant for all). In semaglutide-treated patients, improvements in KCCQ-CSS, 6MWD and CRP were greater with larger body weight reduction (for example, 6.4-point (95% confidence interval (CI): 4.1, 8.8) and 14.4-m (95% CI: 5.5, 23.3) improvements in KCCQ-CSS and 6MWD for each 10% body weight reduction). In participants with obesity phenotype of HFpEF, semaglutide improved symptoms, physical limitations and exercise function and reduced inflammation and body weight across obesity categories. In semaglutide-treated patients, the magnitude of benefit was directly related to the extent of weight loss. Collectively, these data support semaglutide-mediated weight loss as a key treatment strategy in patients with obesity phenotype of HFpEF. ClinicalTrials.gov identifier: NCT04788511 .
Keywords: hmotnostní úbytek; Humans; C-reaktivní protein; Heart Failure; C-Reactive Protein; Weight Loss; tepový objem; Obesity; tělesná hmotnost; obezita; srdeční selhání; Stroke Volume; Body Weight; lidé